PROBLEMS OF DEVELOPMENT OF INNOVATIVE ACTIVITY OF THE MINING AND METALLURGICAL COMBINE - U. D. Gayratov (Bright Mind Publishing, 2025)
The article examines the main problems hindering the development of innovative activities of mining and metallurgical plants. The economic, technological, and organizational barriers to innovation in the industry are analyzed. The key factors influencing the level of innovation activity are identified, and ways to overcome them are proposed.
Keywords: Innovations, mining and metallurgical plant, technologies, modernization, investments, sustainable development.